Articular Joint-Simulating Mechanical Load Activates Endogenous TGF-β in a Highly Cellularized Bioadhesive Hydrogel for Cartilage Repair. Issue 1 (January 2020) - Behrendt, Peter; Ladner, Yann; Stoddart, Martin James; Lippross, Sebastian; Alini, Mauro; Eglin, David; Armiento, Angela Rita
Background: The treatment of osteochondral defects (OCDs) constitutes a major problem for orthopaedic surgeons. The altered mechanics and the cell types, with associated soluble factors derived from the exposed subchondral bone, are likely responsible for the mechanically and structurally inferior articular cartilage subsequently obtained as a repair tissue. There is therefore an unmet clinical need for bioresponsive biomaterials that allow cell delivery, reduce cell infiltration from the bone marrow, and support chondrogenesis in the presence of joint mechanical loading. Purpose: To develop a cell-laden injectable biomaterial, with bioadhesive properties, low cell invasion, and good mechanoresilience, in which simulated joint loading could induce tissue maturation through the production and activation of transforming growth factor beta 1 (TGF-β1). Study Design: Controlled laboratory study. Methods: Human bone marrow–derived mesenchymal stromal/stem cells were encapsulated in tyramine-modified hyaluronic acid (HA-Tyr) hydrogels, with crosslinking initiated by the addition of horseradish peroxidase (HRP) and various concentrations of hydrogen peroxide (H2 O2 ; 0.3-2 mM). Cytocompatibility and biomechanical and adhesive properties were analyzed by live/dead staining, rheology, and push-out test, respectively. For multiaxial loading, cell-laden hydrogels were subjected to 10% compression superimposed onto a 0.5-N preload and shear loading (±25°) at 1 Hz for 1 hour per day and 5 times a week for 4 weeks. TGF-β1 production and activation were measured by enzyme-linked immunosorbent assay (ELISA). Results: The viscoelastic properties of the cell-laden HA-Tyr hydrogels, as crosslinked with different ratios of HRP and H2 O2, were demonstrated for a range of cell densities and HRP/H2 O2 concentrations. In the absence of serum supplementation, cell invasion into HA-Tyr hydrogels was minimal to absent. The bonding strength of HA-Tyr to articular cartilage compared favorably with clinically used fibrin gel. Conclusion: HA-Tyr hydrogels can be mechanically conditioned to induce activation of endogenous TGF-b1 produced by the embedded cells. HA-Tyr hydrogels function as cell carriers supporting biomechanically induced production and activation of TGF-β1 and as bioadhesive materials with low cell invasion, suggesting that they hold promise as a novel biomaterial for OCD repair strategies. Clinical Relevance: Leveraging physiological joint mechanics to support chondrogenic graft maturation in an optimized mechanosensitive hydrogel in the absence of exogenous growth factors is of highest interest for OCD repair.